2019
DOI: 10.1007/s42729-019-00154-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nitrogen Availability on a Tropical Peat Soil Cultivated with Ananas comosus L. Merr. Using Pineapple Residue Ash

Abstract: The objectives of this study were to use pineapple residue ash to (i) reduce ammonium and nitrate leaching and (ii) improve essential nutrient availability on a tropical peat soil under pineapple cultivation. Laboratory leaching experiments were carried out to determine the effectiveness of pineapple residue ash in controlling nitrogen loss from a tropical peat soil. Ion exchange resin method was used to determine nitrogen availability. Treatments evaluated were (i) different amounts of pineapple residue ash (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The effect is related to the high internal porosity, high surface charge density, large surface area, and multiple functional groups, which aid the P adsorption [212,213]. Scanning electron microscopy (SEM) micrographs showed that the ash derived from pineapple residues also has porous structures [214]. The highly porous structure of charcoal and wood ash indirectly enhances P availability because they can capture and hold P-rich water, thus preventing them from leaching out.…”
Section: Retention Of Phosphorus-rich Water By Porous Structure Of Charcoal and Wood Ashmentioning
confidence: 99%
“…The effect is related to the high internal porosity, high surface charge density, large surface area, and multiple functional groups, which aid the P adsorption [212,213]. Scanning electron microscopy (SEM) micrographs showed that the ash derived from pineapple residues also has porous structures [214]. The highly porous structure of charcoal and wood ash indirectly enhances P availability because they can capture and hold P-rich water, thus preventing them from leaching out.…”
Section: Retention Of Phosphorus-rich Water By Porous Structure Of Charcoal and Wood Ashmentioning
confidence: 99%
“…Those organic residues with high ratios of C/N immobilized the mineral nitrogen resulting in suppressed levels of nitrogen in the amended soil. Besides, Choo et al (2020) described that lower rates of organic waste (pineapple residue ash) increased the nitrogen uptake by tested plant (Ananas comosus L. Merr.).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, the use of crop residues in soil is a common practice in agriculture. This is believed to be beneficial to soil carbon sequestration while improving physico-chemical properties of the soil and crop yield 143,144 . However, crop residues are known to be one of the major sources of N 2 O emissions in agricultural ecosystems.…”
Section: Emission Inventorymentioning
confidence: 99%